PROBLEMS OF FORMATION OF INTER-CULTURAL LITERACY OF STUDENTS AT THE UNIVERSITY - L. Kuvaeva (Вестник Северо-Кавказского федерального университета)
The article considers the intercultural literacy of students as the main competence of a modern specialist. The author analyzes the theory of cultural literacy by E. D. Hirsch and the concept of intercultural literacy, as well as the features of using a multidisciplinary approach in its formation. The author indicates the special role of the cultural context in the formation of intercultural literacy, and in the study of a foreign language in particular. A number of problems of the formation of intercultural literacy among university students through the discipline «foreign language» are formulated, such as: the predominance of a communicative approach in modern teaching methods; the prevalence of the traditional disciplinary approach in universities; fragmentation of the study of grammar and vocabulary; low level of motivation of cognitive activity of students, aimed at the formation of intercultural literacy. The article draws attention to the fact that the formation of intercultural literacy is not highlighted as an independent component of student learning goals.